Investigation of the level of safety and appropriateness of playgrounds in Elazig city in Turkey - Açik, Y; Gülbayrak, C; Çelik, GT (Carfax Publishing, 2004)
This study was conducted to identify and evaluate the degree of appropriateness of children's playground standards and the level of compliance with the current safety specifications of the playgrounds in Elazig city in Turkey. This was accomplished by on-site observation and measurement in the total of 24 playgrounds present in this city centre. It was determined that 83.3% of the playgrounds were next to a street and in 60% of these playgrounds there were no fences or any barrier to keep children from running into the street. In 87.5% of playgrounds the surfacing was not in proper depth and good order. Separate playgrounds for different ages were provided in only 12.5% of the playgrounds. In 62.5% of the playgrounds children were supervised to make sure they were safe. There was unsafe equipment in 95.8% of the playgrounds. In 83.3% of the playgrounds there were sharp edges, pinch points, or playground debris that might injure a child. The findings of the present study indicate that nearly all of the playgrounds in Elazig city center do not meet the criteria for playground standards and are not in compliance with the current safety specifications and need improvement.
Keywords: children; playground; safety